Roland Barthes’ Semiotic Theory: The Potrayal of Femininity in the Film Aladdin (2019) - Nurfahresi, Cinta Auralia; Prastiwi, Yeny (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Films are often seen as mere entertainment, but they can carry hidden messages and meanings, making them a medium of mass communication. Disney have a big influence on gender perceptions, shapes views on gender roles more powerfully than schools or families. This study aims to analyze the representation of feminism in Disney’s “Aladdin” (2019). This research was conducted using Roland Barthes Theory, namely by using denotative, connotative, and myth meanings. The results of this study divided in six findings, there are: (1) Equality Between Woman and Men; (2) Belief in Women as Leaders; (3) Oppressing Women in the Name of Tradition; (4) The fate of being a Woman; (5) The Price of a Woman; (6) Women and Freedom.